2010
DOI: 10.1172/jci42945
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic T cells have a paradoxical protective effect in murine autoimmune diabetes by boosting Tregs

Abstract: CD4 + CD25 + Foxp3 + Tregs play a major role in prevention of autoimmune diseases. The suppressive effect of Tregs on effector T cells (Teffs), the cells that can mediate autoimmunity, has been extensively studied. However, the in vivo impact of Teff activation on Tregs during autoimmunity has not been explored. In this study, we have shown that CD4 + Teff activation strongly boosts the expansion and suppressive activity of Tregs. This helper function of CD4 + T cells, which we believe to be novel, was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
134
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(147 citation statements)
references
References 58 publications
(69 reference statements)
13
134
0
Order By: Relevance
“…Signaling through TNFR2 then leads to expansion of regulatory T cells that protect NOD mice from diabetes. Our data are compatible with the recent study showing that blockade of TNF reduced the proliferation of regulatory T cells and that TNF secreted by effector T cells boosted the expansion of regulatory T cells (23). To prove our hypothesis, Table I shows the strain and number of mice in each group that underwent GK1.5 treatment and developed T1D.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Signaling through TNFR2 then leads to expansion of regulatory T cells that protect NOD mice from diabetes. Our data are compatible with the recent study showing that blockade of TNF reduced the proliferation of regulatory T cells and that TNF secreted by effector T cells boosted the expansion of regulatory T cells (23). To prove our hypothesis, Table I shows the strain and number of mice in each group that underwent GK1.5 treatment and developed T1D.…”
Section: Discussionsupporting
confidence: 91%
“…One of the effects of TNF-TNFR2 signaling is the promotion of T regulatory cell expansion (22). It has been shown recently that activated autoreactive T effectors secrete TNF-a, which induces an expansion of T regulatory cells via TNF-TNFR2 interactions (23). This is one of the proposed mechanisms for fine tuning the balance between effector T cells and the regulatory T cells to control autoimmune diseases such as multiple sclerosis and diabetes.…”
mentioning
confidence: 99%
“…It has been reported previously that TNFR2 2/2 nTregs are able to suppress normally in vitro (14). In this study, we find no phenotypic differences between WT and TNFR2 2/2 nTregs that would account for the abnormal in vivo function of TNFR2 (19) showing that TNF-a is necessary for optimizing, or "boosting," Treg function in the context of autoimmunity, rather than being required for the baseline functioning of Tregs. Furthermore, TNFR2 2/2 mice demonstrate exacerbated disease when induced to develop experimental autoimmune encephalomyelitis, further suggesting that the anti-inflammatory effects of TNF-a are mediated through TNFR2 (36).…”
Section: Preactivation Of Tnfr2supporting
confidence: 52%
“…Although reports have shown opposite effects of TNF-a on mouse and human Tregs, both mouse and human studies have suggested that TNFR2 is the primary receptor required for these effects. Recently, using murine models of diabetes, Grinberg-Bleyer et al (19) demonstrated that the suppressive function of Tregs is optimized by the presence of Teffs and that TNF-a is one factor involved in this optimization (19,20). In this study, we have investigated the role of TNFR2 on both murine nTregs and iTregs in the in vivo suppression of autoimmunity.…”
mentioning
confidence: 92%
“…Within these transcripts, the Tnfrsf1b (TNFR2) transcript was most intriguing because TNF-a has recently been shown to promote Treg cell expansion and activation in the inflammatory microenvironment through TNFR2 in an antigen-nonspecific way. 8 Correlating with the gene expression results, by flow cytometric analysis, the CD103 C Treg cells expressed higher levels of TNFR2 when compared with CD103 ¡ Treg cells in spleen (Fig. 4B) and tumor microenvironment (Fig.…”
Section: Cd103supporting
confidence: 58%